EFEKTIVITAS TERAPI RENANG GAYA BEBAS TERHADAP PENINGKATAN MOTORIK KASAR ANAK AUTIS SWIMMING CLUB TIRTO KARIMUN - Harini, Aprilia Setya; Huda, Maftukin; Widyatmoko, Fajar Ari (YLPK Mahardhika, 2025)
This study aims to evaluate the effectiveness of freestyle swimming therapy on improving gross motor skills in children with autism who are members of the Swimming Club Tirto Karimun. This study uses an experimental method with a Single Subject Research (SSR) design of type A-B-A. The study subjects consisted of a child with autism who participated in a swimming therapy program for seven sessions. Data were collected through observation using the Gross Motor Function Measure (GMFM) instrument which was modified and analyzed using the visual analysis method and Percentage of Non-overlapping Data (PND). The results showed that before the intervention, the child's gross motor skills were at a level of 91%, and after the intervention, it increased to 100%. This increase occurs gradually, especially in the aspects of balance, coordination, and body awareness. These results show that freestyle swimming therapy provides significant benefits in developing gross motor skills in children with autism. Therefore, freestyle swimming therapy can be used as one of the effective intervention approaches in the rehabilitation program of children with autism.